Use of learning objects digital for flexibilize the knowledge and potentialize the autonomy of learning in teaching of environmental education - Fiuza, Deise Quiele Rauber; Muller, Liziany Medeiros; Rech, Aline Pereira de Arruda; Machado, Andreia Oliveira (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
Despite the importance of environmental education (EE) in formal education, it is still weak in teaching practice and much contingent on the use of technology. Thus, this study aims to evaluate the contribution and on the potential use of digital learning objects in teaching environmental education, involving elementary school students of the Colégio Franciscano Sagrado Coração de Jesus, in Arroio do Tigre city. The technology use can result in several contributions to education, such as: student autonomy in the learning process and their inclusion in the digital world. The learning objects propose the use of digital awareness activities through the use of technology with virtual practical activities related to environmental issues, sustainability, fashion, consumerism and waste. Starting from a premise location, but not leaving consider the environment in its multiple aspects, with a broad range of regional and global, was applied to calculate the carbon footprint and environmental education videos built to be virtually spread social networks and Youtube.